Bamlanivimab improves hospitalization and mortality rates in patients with COVID-19: A systematic review and meta-analysis. Issue 2 (February 2022) - Zuo, Ling; Ao, Guangyu; Wang, Yushu; Gao, Ming; Qi, Xin
Highlights: All studies compared Bamlanivimab monotherapy vs. control group. A total of 8 studies comprising of 13, 573 adult patients with COVID-19 were included. Outcomes suggested Bamlanivimab improved hospitalization and mortality rates.